Экономический потенциал Украины и пути его реализации в условиях кризиса - Рябыкина, Н.И.; Ревва, А.Н.; Булеев, В.Е. (Стратегія і механізми регулювання промислового розвитку, 2016)
Выполнен ретроспективный обзор функционирования экономики Украины после обретения самостоятельности. Установлены причины системного социально-экономического кризиса, важнейшей среди которых является кризис интеллекта. Доказано, что Украина должна изменить хозяйственный механизм, институты управления, адаптируя их к реальным условиям капиталистического способа производства. Исследованы основные противоречия интересов классов, групп населения на данном этапе реформирования экономики. Особое место и значение имеет противоречие между олигархами (группами олигархов), а также между группами олигархов и государством как коллективным капиталистом. Изложены основные направления интенсификации использования имеющегося экономического потенциала и его инновационного развития. Виконано ретроспективний огляд функціонування економіки України після набуття самостійності. Встановлено причини системної соціально-економічної кризи, найважливішою серед яких є криза інтелекту. Обґрунтовано, що Україна має змінити господарський механізм, інститути управління, адаптуючи їх до реальних умов капіталістичного способу виробництва. Досліджено основні протиріччя інтересів класів, груп населення на даному етапі реформування економіки. Особливе місце і значення має протиріччя між олігархами (групами олігархів), а також між групами олігархів і державою як колективним капіталістом. Викладено основні напрями інтенсифікації використання наявного економічного потенціалу та його інноваційного розвитку. Analysis of indicators of socio-economic development of Ukraine since the 90s of the XX century. To the present time indicates a systemic crisis of the economy and society. This was the result of ill-conceived actions, both in the choice of the management system that corresponds to the level of development of the productive forces, and mistakes in the choice of the mainstream economic theory, which corresponds to the mentality of the people and the accepted state arrangement. The most important mistakes made: the illegitimacy of denationalization and privatization of fixed assets, which led to a dangerous differentiation of the population in terms of income and further alienation of employees from participation in property and management; Ignoring the need for a radical transformation of political, social and civic institutions; Sharp restriction of financing of science, education, health; Loyal attitude to corruption and bureaucracy; Misunderstanding of the role of the domestic market in preserving and developing the production and economic potential, etc. As a result, over the past 25 years, Ukraine has moved from the twenty most economically developed countries of Europe to the very end of international ratings, has become an agrarian country in which the confrontation of groups of people is brought to an open armed conflict.The most important directions of Ukraine 's exit from the social and economic crisis are substantiated. This is an immediate cessation of the armed conflict in the South-East of Ukraine; The formation of the middle class and civil society; Development of the domestic market by increasing the purchasing power of the population; Formation of state-corporate property and large integrated integrated structures on the world markets; Development of small and medium-sized business in the real sector of the economy; The use of the gross value added (GVA) in enterprise performance assessment; Attraction of workers to participation in management and in capital, etc. Maximize the use of the remaining production capacities, and direct profits and GVA to the development of production of V-VI technological structures, science, education, health.